A study on the quality of front office service at Renaissance Kota Bharu Hotel / Nur Haslina Ramli - Ramli, Nur Haslina (Faculty of Business and Management, 2008)
The research was conducted with the objective to determine the flour ofiice service quality at Renaissance Kata Bharu Hotel. The researcher has selected four variables as the factors that determine the quality of front office at Renaissance Kata Bharu Hotel which are courtesy, responsiveness, skill and assurance, Among than four, the researcher also tried (a investigate the front office service quality from the view of customer's perspective‘ 0n the other hand the researcher tried to evaluate the relationships among these variables to the front office service quality of Renaissance Kata Bharu Hotel. For this purpose, a research survey by using a structural questionnaire was conducted to gather the information required which could provide the answer to the subject marten There were 100 questionnaires collected from the respondetns who used front office service at Renaissance Kora Bharu Hotel.